2005
DOI: 10.1080/00207230500367879
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and daily hospitalization rates for cardiovascular and respiratory diseases in London, Ontario

Abstract: In this paper, we examine the role that ambient air pollution plays in exacerbating cardiovascular and respiratory disease hospitalization in London, Ontario from 1 November 1995 to 31 December 2000. The number of daily cardiac and respiratory admissions was linked to concentrations of air pollutants (sulphur dioxide, nitrogen dioxide, ozone, carbon monoxide, coefficient of haze, PM 10 ) and weather variables (maximum and minimum of temperature and humidity). Results showed that current day carbon monoxide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
4
19
0
1
Order By: Relevance
“…Correspondingly, some studies [80] indicate correlation between PM exposures with respiratory diseases in older adults. Controlled epidemiological studies of human exposures to PM 2.5 concentrated ambience among older adults indicated decreased heart rate variability (HRV) with or without accompanying COPD [81,82]. Furthermore, some epidemiological studies have shown an association of short-term PM 2.5 [83] and PM 10 [84,85] exposure among older adults ≥75 years, with the progression of health effects from early stages to cardiovascular-related hospitalization or respiratory-related hospitalization and eventual non-accidental death.…”
Section: Children and Older Adultsmentioning
confidence: 99%
“…Correspondingly, some studies [80] indicate correlation between PM exposures with respiratory diseases in older adults. Controlled epidemiological studies of human exposures to PM 2.5 concentrated ambience among older adults indicated decreased heart rate variability (HRV) with or without accompanying COPD [81,82]. Furthermore, some epidemiological studies have shown an association of short-term PM 2.5 [83] and PM 10 [84,85] exposure among older adults ≥75 years, with the progression of health effects from early stages to cardiovascular-related hospitalization or respiratory-related hospitalization and eventual non-accidental death.…”
Section: Children and Older Adultsmentioning
confidence: 99%
“…This work aroused great concern among the local people, public health professionals and government agencies. This in turn led to a number of other studies that examined the association between ambient air quality and health effects in Windsor [8,9]. These studies reported, among other things, short-term effects of air pollutants on daily cardiac and respiratory hospital admissions among the people in Windsor.…”
Section: Rrr Rrmentioning
confidence: 95%
“…Additionally, previous noise mapping of the border corridor showed that traffic along Huron Church Road, which is the main access road to the bridge crossing, has a significant impact on noise levels in the surrounding neighbourhoods (Novak et al, 2009). Effects of air pollution on health have also been observed, with increased rates of cardiac hospitalization from short-term increases in ambient concentrations, and increased levels of respiratory hospitalizations in the months following 9/11 when heightened security measures resulted in exceptionally long crossing queues in the corridor area (Fung et al, 2005;Luginaah et al, 2006a).…”
Section: Objectives and Study Contextmentioning
confidence: 96%